Permen Hisap Propolis (Apis mellifera) sebagai Bahan Alternatif untuk Kontrol Plak Gigi - Pipiet Okti Kusumastiwi; Ajeng Prameswari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2015)
Dental plaque is a soft layer consist of the accumulation of  bacteria, formed and attached to the tooth surface. Propolis (Apis mellifera) contain flavonoid which is known as an antibacterial compound. The content of tt-farnesol and apigenin in flavonoids have a high potential as an anti-Streptococcus mutans and inhibit glucosyltransferase activity.Research objective is To find the influenceof propolis(Apis mellifera) hardcandyconsumption toward the decrease of dental plaquescores.This research was aclinicalexperimentalresearchusing apretest-posttest design. Subjects wererecordedtheirinitialdentalplaquescores,  then consumed propolis(Apis mellifera) hard candy and subjects dental plaque were re-scored. The statisticalanalysis testapplied paired t-test.Theresearch finding showed the meanscores of dental plaquebeforewas 0.47andafter was 0.36 which had 0.10differencesplaque scores with Standar Deviation0,15 and 0,17 respectively.Conclusion wasPropolis(Apis mellifera) hard candy consumption hasthe influence toward thedecreaseof dental plaquescores.